Assessment of Greenhouse Gases Emission in Maize-Wheat Cropping System Under Varied N Fertilizer Application Using Cool Farm Tool - Kumar, Rakesh; Karmakar, S.; Minz, Asisan; Singh, Jitendra; Kumar, Abhay; Kumar, Arvind (Frontiers in Environmental Science, 2021)
In recent decades, climate change induced by enhanced global warming is one of the biggest challenges at the global level. Agriculture sectors significantly contribute to total anthropogenic greenhouse gas emission to the atmosphere. Wheat and maize, cultivated globally, and consumed in different forms, are considered as crucial staple cereal for ensuring food security to global population. The management practices involving land preparation, sowing, fertilizer application, irrigation, pest management, etc. significantly influence the emission of carbon dioxide (CO2) and nitrous oxide (N2O) from agricultural soil. In this study, CO2 and N2O emission were assessed from maize and wheat crops at four different levels of N fertilizer using cool farm tool model. Emissions of CO2 per hectare varied from 331.4 to 1,088.3 kgCO2 in maize and ranged from 292.3 to 765.3 kgCO2 in wheat on application of different doses of N. The total GHG emission in maize crops ranged from 859.5 to 3,003.4 kgCO2 eq per hectare with the application of nitrogen at varying levels (0–240 kg N per hectare). The highest N2O efflux (0.368 kg per ton) was observed at 240 kg N per hectare under wheat crop. The total on-farm emissions, through fertilizer production, account for about 33.7%, and emission of N2O contributes only 65.9%, whereas pesticides account merely 0.4% under maize-wheat cropping. This study confirms that the direct emission of N2O was totally dependent on N fertilizers application rate; however, the indirect emission was controlled by the fuels and energy consumption.